Translation Error of Thai Folktales into Indonesian Language by Asean Studies College Students Walailak University Thailand - Sirirawadee Boonyakiat; A. Syukur Ghazali; Gatut Susanto (Jurnal Pendidikan Humaniora, 2018)
Abstract: This study aims to describe the error of translation Thai folklore texts into Indonesian language by Thai students which in the results of the translation are divided into two analysis as follows: the mistake of word selection and the mistake of composing the sentence. This research use approach and descriptive qualitative research type. Mistakes are mostly caused by the lack of comprehension of Indonesian language as a target language, especially Indonesian language in various contexts minimized the vocabulary of Indonesia language by Thai studentsKey Words: error in translation, Thai language folktales texts Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kesalahan penerjemahan teks cerita rakyat bahasa Thai ke dalam bahasa Indonesia oleh mahasiswa Thailand yang muncul dalam hasil terjemahan terbagi menjadi dua analisis, yaitu: kesalahan pemilihan kata dan kesalahan penyusunan kalimat. Penelitian ini menggunakan pendekatan dan jenis penelitian kualitatif deskriptif. Kesalahan banyak disebabkan oleh minimnya pemahaman ketatabahasan bahasa Indonesia sebagai bahasa sasaran, terutama bahasa Indonesia dalam berbagai konteks serta minimnya kosa kata dalam bahasa Indonesia yang dimiliki oleh mahasiswa Thailand.Kata kunci: kesalahan terjemahan, teks cerita rakyat bahasa Thai